2016
DOI: 10.1063/1.4959562
|View full text |Cite
|
Sign up to set email alerts
|

Superluminescent light emitting diodes on naturally survived InGaN/GaN lateral nanowires

Abstract: We demonstrate a method for nanowire formation by natural selection during wet anisotropic chemical etching in boiling phosphoric acid. Nanowires of sub-10 nm lateral dimensions and lengths of 700 nm or more are naturally formed during the wet etching due to the convergence of the nearby crystallographic hexagonal etch pits. These nanowires are site controlled when formed in augmentation with dry etching. Temperature and power dependent photoluminescence characterizations confirm excitonic transitions up to ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…III‐Nitride materials and devices have attracted a lot of interest due to their immense potential in electronic and optoelectronic applications. (In,Al)GaN based heterostructures have been found suitable for high power, high frequency and optoelectronic device applications . With a lot of advancements made in the growth technology over several years, it is possible to grow good quality heterostructures suitable for device applications .…”
Section: Introductionmentioning
confidence: 99%
“…III‐Nitride materials and devices have attracted a lot of interest due to their immense potential in electronic and optoelectronic applications. (In,Al)GaN based heterostructures have been found suitable for high power, high frequency and optoelectronic device applications . With a lot of advancements made in the growth technology over several years, it is possible to grow good quality heterostructures suitable for device applications .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Using a variety of growth techniques, 9,10 AlN and its alloys Al x Ga 1x N (0 < x ≤ 1) are expected to facilitate the fabrication of more sensitive UV photodetector devices, 11,12 ultralow-threshold UV lasers, 13 and reduce polarization fields. 14,15 GaN-based nanowire devices have high quantum efficiencies, 16,17 sharp peaks of density of states at the lowest quantized sub-band energy levels, 18 improved exciton binding energy, 19 and increased wavefunction overlap of the electron-hole pairs. 20 Moreover, designing heterojunctionbased optoelectronic devices through the integration of three-dimensional (3D) group-III-nitride 25 They argued that the p-type conduction is dominated by hopping conduction.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based light sources for the entire spectra of infrared to ultraviolet wavelengths are being investigated to understand various fundamental material and physical properties and their applications. GaN-based nanostructures are the natural choices for the additional degree of freedom provided by quantum confinement. Among various reduced dimensional structures, quantum wells (QWs), lateral and vertical quantum nanowires, and quantum dots (QDs) are more frequently used for their reproducibility in growth, ease of device fabrication on these structures, and physical properties. QDs provide many significant advantages, including higher gain through impulse like density-of-states, higher strain relaxation, indium- and aluminum-rich heterostructures for longer and shorter wavelengths, bridging the green gap, larger surface to volume ratio, improved external quantum efficiency, and potential use in quantum technology as a single-photon source. The QD light-emitting diodes using the most popular InGaN/GaN heterostructures are being investigated in various forms, and they have been proven to demonstrate superior light-emitting characteristics in various aspects. Most of the studies are based on continuous wave emission characteristics, and few of them have reported transient luminescence characteristics. The QDs are also frequently grown epitaxially in the form of an array where they are laterally coupled through the barrier layer.…”
mentioning
confidence: 99%